Budaya Pembiasaan Sebagai Upaya Penanaman Nilai Pancasila di SDN 1 Pakunden Kota Blitar - Apriana Ekananda Almasah; Afina Nilna Muna; Ayu Regita Dwi Cahyani; Surayanah (Yayasan pendidikan dzurriyatul Quran, 2026)
Character education has an important role in shaping the morals and behavior of elementary school students in accordance with Pancasila values. Habituation culture in schools is one of the efforts that can be implemented to instill character values in students’ daily lives. This study aims to determine the implementation of habituation culture as an effort to instill Pancasila values in students at SDN 1 Pakunden. This study used a descriptive qualitative approach with field observation research. Data collection techniques included observation, interviews, documentation, and questionnaires, while data analysis used the Miles and Huberman model, which consists of data collection, data reduction, data presentation, and drawing conclusions. The results showed that habituation culture was implemented through routine activities such as praying before and after learning, maintaining cleanliness, classroom duty schedules, cooperation, and flag ceremonies. These activities were able to instill religious values, discipline, responsibility, tolerance, unity, and deliberation among students. The teacher’s role in providing examples and guiding student behavior also supported the success of habituation culture in schools. However, there were still several obstacles, such as students’ lack of confidence in expressing opinions and the influence of social media on character building. Therefore, habituation culture is considered effective in supporting the internalization of Pancasila values in elementary school students Keywords: habituation culture, Pancasila values, character education, elementary school. Pendidikan karakter memiliki peran penting dalam membentuk moral dan perilaku peserta didik sekolah dasar sesuai dengan nilai-nilai Pancasila. Budaya pembiasaan di sekolah menjadi salah satu upaya yang dapat dilakukan untuk menanamkan nilai-nilai karakter dalam kehidupan sehari-hari siswa. Penelitian ini bertujuan untuk mengetahui penerapan budaya pembiasaan sebagai upaya penanaman nilai-nilai Pancasila pada siswa di SDN 1 Pakunden. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan jenis penelitian observasi lapangan. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dokumentasi, dan angket, sedangkan analisis data menggunakan model Miles dan Huberman yang meliputi pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa budaya pembiasaan diterapkan melalui kegiatan rutin seperti berdoa sebelum dan sesudah pembelajaran, menjaga kebersihan, piket kelas, kerja sama, dan upacara bendera. Kegiatan tersebut mampu menanamkan nilai religius, disiplin, tanggung jawab, toleransi, persatuan, dan musyawarah pada peserta didik. Peran guru dalam memberikan teladan dan membimbing perilaku siswa juga mendukung keberhasilan budaya pembiasaan di sekolah. Meskipun demikian, masih terdapat beberapa kendala seperti kurangnya keberanian siswa dalam menyampaikan pendapat dan pengaruh media sosial terhadap pembentukan karakter. Dengan demikian, budaya pembiasaan dinilai efektif dalam mendukung internalisasi nilai-nilai Pancasila pada peserta didik sekolah dasar.